Challenges and Strategies for Post-COVID-19 Gender Equity and Sustainable Mobility - González-Sánchez, Guadalupe; Olmo-Sánchez, María Isabel; Maeso-González, Elvira (MDPI, 2021)
The COVID-19 pandemic has forced countries around the world to take unprecedented measures to contain it. In particular, its impact on mobility has been enormous, causing a sudden decrease in the number of trips and changes in the choice and use of modes of transport. Furthermore, the effects of this health crisis on the social and economic spheres have aggravated inequalities between population groups, with women being one of the most affected groups, which may accentuate the already known gender gap in mobility. Based on these premises, we carried out a strategic analysis of urban mobility from the perspective of sustainability and gender equity in the context of the pandemic, identifying a set of effective strategies to address the post-COVID-19 urban mobility scenario. To this end, based on the review of the literature and expert opinions, we carried out a Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis that allowed us to formulate 16 strategies after careful consideration of the weaknesses, strengths, threats and opportunities encountered. Our results provide useful recommendations for making successful policy decisions on post-COVID-19 mobility planning towards a more sustainable, equitable and safe model.
Keywords: Desplazamientos domicilio-trabajo; Pandemia de la Covid-19, 2020- - Aspectos sociales; Sexismo; Strategies; SWOT analysis; Sustainable urban mobility; COVID-19; Mobility; Gender equity